2001
DOI: 10.1016/s0304-8853(00)00987-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation and magnetization field dependence measurements in La0.5Ca0.5MnO3

Abstract: We reported a systematic change in the average magnetic relaxation rate, after the application and removal of a 5 T magnetic field, in a polycrystalline sample of La 0.5 Ca 0.5 MnO 3 . Magnetic relaxation measurements and magnetization versus field curves were taken from 10 K to 160 K. The long time behavior of the relaxation curves was approximately logarithmic in all cases.Charge ordering compounds have a large variation of resistivity and magnetization as a function of temperature and magnetic field 1,2 .A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In two previous reports 3,4 we showed that polycrystalline samples of La 0.5 Ca 0.5 MnO 3 and Nd 0.5 Sr 0.5 MnO 3 also presented an unusual magnetic relaxation behavior after applying and turning off a 5 T magnetic field. Here, we briefly report specific heat measurements at low temperatures and zero magnetic field for Although it is tenting to establish a straight forward correlation between the intrinsic 10 .…”
mentioning
confidence: 57%
“…In two previous reports 3,4 we showed that polycrystalline samples of La 0.5 Ca 0.5 MnO 3 and Nd 0.5 Sr 0.5 MnO 3 also presented an unusual magnetic relaxation behavior after applying and turning off a 5 T magnetic field. Here, we briefly report specific heat measurements at low temperatures and zero magnetic field for Although it is tenting to establish a straight forward correlation between the intrinsic 10 .…”
mentioning
confidence: 57%
“…With increase in x, La 1 − x Ca x MnO 3 shifts from insulating to metallic behaviour. But at x = 0.5, where Mn 3+/4+ ratio is 1:1, charge ordered (CO) insulating state [6,7] occurs where manganese ions align themselves in an ordered pattern and thus hampering the movement/hopping of conduction electrons. However, on application of magnetic field, this CO state melts down giving rise to huge magnetoresistance (MR) below T CO [4].…”
Section: Introductionmentioning
confidence: 99%
“…6 We have shown that polycrystalline samples of La 0.5 Ca 0.5 MnO 3 and Nd 0.5 Sr 0.5 MnO 3 presented an unusual magnetic relaxation behavior close to each critical temperature. 7,8 However, a clear understanding of all these features has not been reached yet. An alternative to a bulk characterization like magnetization would be to perform specific-heat measurements.…”
Section: Introductionmentioning
confidence: 99%